Strong summability of orthogonal expansions of summable functions. I - Lasuriya, R. A.; Stepanets, O. I. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We study the problem of strong summability of Fourier series in orthonormal systems of polynomial-type functions and establish local characteristics of the points of strong summability of series of this sort for summable functions. It is shown that the set of these points is a set of full measure in the region of uniform boundedness of systems under consideration.